Effectiveness of a Self-Instructional Module on Knowledge Regarding Self-Care Management among Patients with Chronic Kidney Disease in Nepal - Sunar, Tulasa; Khadka, Rekha; Sapkota, Srijana; Ghimire, Nisha (AMC Multidisciplinary Research Journal, 2025)
Chronic kidney disease (CKD) is a major public health issue in Nepal, with an estimated prevalence of 10.6% in urban areas. Globally, the incidence of End-Stage Renal Disease (ESRD) has been increasing by approximately 7.8% per year. Effective self-care management is crucial in slowing disease progression and preventing complications. This study aimed to assess the effectiveness of a self-instructional module (SIM) on knowledge regarding self-care management among CKD patients. A pre-experimental one-group pretest-posttest design was used. The study was conducted at Bheri Hospital, Nepalgunj, from March 2023 to August 2023. A total of 160 CKD patients were selected using non-probability purposive sampling. Data were collected using a structured questionnaire assessing socio-demographics, clinical profile, and knowledge regarding self-care management. The SIM covered topics such as CKD complications, fluid and dietary management, exercise, and weight management. A pretest was conducted on Day 1, followed by administration of the SIM. A posttest was conducted after 6 weeks using the same questionnaire. Data were analyzed using descriptive statistics and inferential tests, including paired t-tests and chi-square tests. The mean pretest knowledge score was 51.8±3.4, which increased significantly to 62±3.2 in the posttest (t = 29.4, p = 0.001). Before the intervention, 32.5% of participants had poor knowledge, and none had a good knowledge score. After the intervention, 68.1% had good knowledge, while no participants remained in the poor knowledge category. Chi-square analysis showed no significant association between socio-demographic variables and knowledge scores. The self-instructional module was effective in enhancing knowledge regarding self-care management among CKD patients. Implementing structured educational interventions in clinical settings can improve patient awareness, adherence to self-care practices, and overall disease management.